Perception and Response to Climate Change by Small Farmers: The Case of Mareko District, Southern Ethiopia: Perception and Response to Climate Change by Small Farmers: The Case of Mareko District, Southern Ethiopia - Gegulo, Doliso Fufula; Gemeda, Dessalegn Obsi; Gebre, Sintayehu Legesse (International Journal of Economic and Environmental Geology, 2019)
Climate change and variability is one of the common challenges of rainfall dependent economic activities like agriculture. In this study, we assessed the perception of small landholders on the impact of climate change and their adaptation strategies in Mareko district in southern Ethiopia. Data were collected from a total of 120 small farmers from two villages in Elala Gebiba and Hobe Jare Dembeka. The results obtained from meteorological data of three decades (1986-2015) show an increase in temperature by 0.39oC and rainfall fluctuations over the last 30 years. Perceptions of these farmers on climate change depend on the level of vulnerability to the extreme events like drought and flooding. The perception of local communities on climate change indicated that there was an increase in temperature (98.3%) in the study area that had a potential impact on their livelihoods. Local people perceived that, the hazards induced by climate change like drought, extreme heat, livestock disease and floods affected their livelihood. The results of this study indicate that changing cropping date, practicing soil and water conservation, shifting from cattle to goats and sheep, income source diversification, growing drought tolerant crops like false banana, millet, sorghum and quicker-maturing crops like haricot bean and vegetables are the major adaptation options in the study area. Thus, this research contributes to the knowledge gaps on potential existing climate change adaptation strategies for those dependent on rain-fed agriculture for their food and livelihoods.